The basic assumptions of Bronisław Rocławski’s glottodidactics and its interdisciplinary application in primary education and speech therapy: a review of literature on the topic - Rocławska-Daniluk, Małgorzata; Kisiel, Weronika (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The system (or otherwise: method) of Bronisław Rocławski’s glottodydactics has been described in many scientific publications. An overview of selected scientific studies on this subject published in Poland after 1996 presents the most important glottodydactics topics. In the summary, the authors made insights about the education crisis, as well as positive attitudes to support.